Autologous transplantation as consolidation for high risk aggressive T-cell non-Hodgkin lymphoma: a SWOG 9704 intergroup trial subgroup analysis. Issue 8 (3rd July 2019) - Al-Mansour, Zeina; Li, Hongli; Cook, James R.; Constine, Louis S.; Couban, Stephen; Stewart, Douglas A.; Shea, Thomas C.; Porcu, Pierluigi; Winter, Jane N.; Kahl, Brad S.; Smith, Sonali M.; Marcellus, Deborah C.; et al.
Abstract: Phase II data suggest a benefit to autotransplantation for aggressive T-cell non-Hodgkin lymphoma (T-NHL) in first remission; randomized trials have yet to validate this. We performed a retrospective analysis of aggressive T-NHL patients in the intergroup randomized consolidative autotransplant trial (SWOG 9704). Of the 370 enrolled, 40 had T-NHL: 12 were not randomized due to ineligibility ( n  = 1), choice ( n  = 2), or progression ( n  = 9), leaving 13 randomized to control and 15 to autologous stem cell transplantation (ASCT). Two ASCT patients refused transplant and one failed mobilization. The 5-year landmark PFS/OS estimates for ASCT vs. control groups were 40% vs. 38% ( p  = .56), and 40% vs. 45% ( p  = .98), respectively. No difference was seen based on IPI, or histologic subtype. Only 1/7 receiving BCNU-based therapy survived vs. 4/5 receiving TBI. Aggressive T-NHL autotransplanted in first remission did not appear to benefit from consolidative ASCT. This and the 30% who dropped out pre-randomization mostly to progression, suggests that improved induction regimens be developed.